The role of leadership in occupational stress - Gentry, William A.; Clerkin, Cathleen; Perrewe, Pamela L.; Halbesleben, Jonathon R. B.; Rosen, Christopher C. (Research in occupational stress and well being ;, 2016)
The objective of this series is to promote theory and research in the increasingly growing area of occupational stress, health and well being, and in the process, to bring together and showcase the work of the best researchers and theorists who contribute to this area. Our goal is to provide a multidisciplinary and international collection that gives a thorough and critical assessment of both knowledge and major gaps in knowledge. Volume 14 of Research in Occupational Stress and Well Being is focused on leadership. Through their actions and behaviors, leaders can positively, or negatively, influence the health, stress, and well being of their followers, and vice versa as well. This volume examines critical topics for a deeper understanding of the intersection of leadership, stress, and well being which include: a leader's dark personality, a leader's networks, workaholism, the role of leaders in helping employees with stress and mental health issues, followership, and a more holistic view of a leader's life at work and away from work, and the development of leaders. The topic of this volume, Leadership, is sure to attract the attention of researchers around the globe.